A Critical Review of YouTube Videos on the Socket-shield Technique: A Content-quality Analysis - Urvi Echhpal; Subhabrata Maiti; Rajendra Prabhu Abhinav (Contemporary Clinical Dentistry)
Dental students often prefer social media for its accessibility and low cost but must critically evaluate the content before applying it in practice. This study analyzed YouTube content on socket shielding. A new Google account was created to search for “Socket Shield Technique” and “Partial Extraction Therapy.” Eligible videos were assessed for quality using the Global Quality (GQ) tool and the DISCERN tool. Statistical analysis was performed using the Statistical Package for the Social Sciences software. Results showed an average of 28.35 likes per video, no dislikes, and substandard content indicated by a DISCERN score of 25.25 ± 2.4 and a GQ score of 1.82 ± 0.38. The study concludes that video content on socket shielding is not reliable, emphasizing the importance of clinical observation and hands-on practice.